ORGANIZATIONAL COMMUNICATION IN REALIZING EFFECTIVE MADRASAH IN JAMBI PROVINCE - Yudo Handoko; Martinis Yamin; Minnah El-Widdah (European Journal of Humanities and Educational Advancements, 2022)
The problem of the quality of education personnel in Madrasah Aliyah Negeri Jambi Province is still found and has implications for effective madrasas that do not meet the standards. The purpose of this study is to analyze organizational communication in realizing an effective madrasa in Madrasah Aliyah Negeri in Jambi Province. This study uses a qualitative descriptive analytical approach. Data was collected by using observation, interview and documentation techniques. Determination of research subjects using purposive sampling technique. Data analysis techniques with data reduction, data presentation and drawing conclusions and verification. Trustworthiness with techniques of extension of participation, thoroughness of observation, triangulation of data and consultation of promoters. The result of this research is that the organizational communication of MAN in Jambi Province has not run optimally because it has not found the ideal format. The MAN program in Jambi Province which is related to education personnel is very dependent on the character of the leadership, not on the management standards set by the government. As a result, the quality of education personnel in working in each madrasa is different and cannot reach the same standard, even though the policies in the government are the same or uniform. The conclusion of the study is that organizational communication in realizing effective madrasas in Jambi Province has not run optimally because the culture and communication climate are not healthy and can foster enthusiasm for measurable changes.